Clusters of the Czech Regions and 31 Chosen European Countries According to the Wage Level; Wage Models and Gender Gap by the Czech Regions - Bílková, Diana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The main aim of this paper is the creation of the clusters of the Czech regions that are close as possible by the wage level in these regions and clusters of 31 chosen European countries according to the same criterion. The Czech regions were clustered into three or five clusters, while the European countries were clustered into three, five or seven clusters. The number of clusters has been selected based on the number of clustered objects and due to the clarity of the results obtained. Using the methods of cluster analysis, the clusters with similar wage level were created. Methods of the furthest neighbour and Euclidean distance metric were used. For the Czech regions, the model wage distribution was constructed to enable the comparison of wage development during recent seven years. Three-parametric lognormal curves present the basis of the theoretical wage distribution. The special attention was paid to the situation of wage level within European countries and its comparison with the wage level in the Czech Republic. The researched variable is the gross monthly (nominal) wage. Database comes from the official website of the Czech Statistical Office
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 27-42
Keywords: clusters of the Czech regions by wage level; clusters of 31 chosen European countries by wage level; wage models in the Czech regions; gender wage gap by the Czech regions; prediction of gender wage gap by the Czech regions